A Comparison of Taped Problems and Explicit Timing Interventions on Second-Grade Students' Subtraction Fluency. Issue 5 (11th October 2022) - Fontenelle, Scuddy; Poncy, Brian C.; Solomon, Benjamin G.; Schutte, Greg; Loethen, Emily
Abstract: An adapted alternating treatments design was used to compare the effects of class-wide applications of Taped Problems (TP) and Explicit Timing (ET) interventions on digits correct per minute (DCPM) scores. The study also investigated whether initial fluency scores would differentiate intervention effectiveness between TP and ET procedures. Results showed that both TP and ET resulted in similar DCPM increases, with both approaches significantly outperforming a control condition. Although the interventions showed similar effectiveness at the class-wide level, the interaction between intervention type and initial fluency levels suggested a differential effect. For students with initial fluency scores in the frustrational range (≤10 DCPM), it was found that TP resulted in a higher growth rate than both ET and the control. For students with initial fluency scores in the instructional range (>10 DCPM), both ET and TP interventions resulted in higher DCPM scores than control but did not differ from one another. The discussion focuses on using skill by treatment interactions to inform intervention selection, explores opportunities and challenges in this research area, and addresses study limitations. Impact Statement This study compares two empirically based interventions, Taped Problems and Explicit Timing, to determine which one is more effective to increase digits correct per minute (DCPM) scores. Results showed that both interventions could be successfully used to increase student DCPM scores but that for students initially scoring below 10 DCPM Taped Problems was more effective.